Evaluation of delta-aminolaevulinic acid in blood of workers exposed to lead. Issue 1 (January 1993) - Takebayashi, T; Omae, K; Hosoda, K; Satoh, T; Hamaguchi, T; Sakurai, H
Abstract : Exposure-effect and exposure-response relation between exposure to lead and delta-aminolaevulinic acid concentration in blood (ALA-B) were examined in 238 male workers exposed to lead. Concentrations of ALA-B ranged from 26 to 352 micrograms/l and lead concentrations in blood (Pb-B) from 7.1 to 86.0 micrograms/dl. Concentrations of ALA-B correlated closely with concentrations of Pb-B (r = 0.74), and increased ALA-B concentration occurred at Pb-B concentrations of around 30 micrograms/dl. Exposure-response curves indicated that the 50 percentile response doses were roughly 30, 40, and 50 micrograms/dl Pb-B when cut off points of ALA-B were set at 50, 60, and 70 micrograms/l respectively. The sensitivity and specificity of measurements of ALA-B concentrations for health screening were sufficiently high when the health based exposure limits of lead were set at 30-50 micrograms/dl. Moreover, a pronounced increase in ALA-B concentrations occurred when the inhibition rate of erythrocyte ALA dehydratase exceeded 85%. These findings suggest that ALA-B is a useful indicator for assessing the early effects of exposure to lead on haem biosynthesis.